2022
DOI: 10.3389/fmed.2022.890206
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical, and Trichoscopic Features of Syphilitic Alopecia: A Retrospective Analysis and Systematic Review

Abstract: BackgroundSyphilitic alopecia (SA), which mimics other types of alopecia, is an uncommon manifestation of secondary syphilis. Trichoscopic features may facilitate its diagnosis. However, studies on SA and its trichoscopic characteristics remain limited.ObjectiveTo investigate the epidemiological, clinical, and trichoscopic findings and laboratory results, treatment, and outcomes of SA in Thai patients as well as to comprehensively summarize all trichoscopic features of SA through a systematic review.MethodsDat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 36 publications
(43 reference statements)
4
5
0
7
Order By: Relevance
“…Results were consistent with those of previous studies that reported short regrowing hairs and black dots as the most prevalent trichoscopic signs for SA and AA, respectively. 5 , 18 , 21–23 Moreover, our findings support that trichoscopic signs of SA are nonspecific and overlap with those of AA. 18 , 23 Exclamation mark hairs, angulated hairs/zigzag hairs, and non-pigmented regrowing hairs provided high specificity and PPV of more than 90% towards AA.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Results were consistent with those of previous studies that reported short regrowing hairs and black dots as the most prevalent trichoscopic signs for SA and AA, respectively. 5 , 18 , 21–23 Moreover, our findings support that trichoscopic signs of SA are nonspecific and overlap with those of AA. 18 , 23 Exclamation mark hairs, angulated hairs/zigzag hairs, and non-pigmented regrowing hairs provided high specificity and PPV of more than 90% towards AA.…”
Section: Discussionsupporting
confidence: 81%
“… 5 , 18 , 21–23 Moreover, our findings support that trichoscopic signs of SA are nonspecific and overlap with those of AA. 18 , 23 Exclamation mark hairs, angulated hairs/zigzag hairs, and non-pigmented regrowing hairs provided high specificity and PPV of more than 90% towards AA. However, only exclamation mark hairs showed high AUC, which favored the diagnosis of AA over SA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Additionally, PRP impacts the anti-inflammatory effect by downregulating monocyte chemoattractant protein-1, matrix metalloproteinase (MMP)-3, MMP-13, and a disintegrin and metalloproteinase with thrombospondin motifs-5, and immunomodulatory properties by upregulating IL (interleukin)-4, IL-10, IL-13, and TGF-β ( 65 68 ). Furthermore, PRP may restore normal skin, prevent fibrosis, and remodel scar tissue ( 69 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Infection of the hair follicles resulting in alopecia of the scalp is present in approximately 10% of patients, and typically presents in a moth-eaten pattern ( Image 6 ). 33 Up to 10% of patients develop condylomata lata ( Image 7 ). 34 , 35 These lesions are mostly skin-coloured and are typically smooth, soft and flat, occurring in warm and moist areas such as the anogenital region, toe webs and oral cavity.…”
Section: Clinical Manifestations Of Syphilismentioning
confidence: 99%